Pengaruh Penambahan Berbagai Jenis Gula dan Ekstrak Kulit Buah Naga Terhadap Kualitas Nata de leri - Ajeng Priyani; Zaenal Abidin; Edi Junaedi (Mahesa Research Center, 2023)
Waste that can be utilized into a product that has economic value. By utilizing rice washing waste water and dragon fruit skin waste, it can be used as a fermented food product called Nata de leri. This study aims to determine the effect of adding various types of sugar and dragon fruit peel extract on the quality of Nata de leri. The method of this study was a randomized factorial block design (RAKF) which consisted of two treatment factors, namely various types of sugar, namely granulated sugar, palm sugar and artificial sweeteners, then the second treatment factor was the addition of dragon fruit peel extract with three levels (15%, 25% and 50). %). The results of the study were analyzed using the thickness test, then continued Duncan's test and obtained a different notation which meant that it was significantly different from the Friedman test. In the Friedman test the texture quality and taste quality did not have a significant effect, while the color quality had a significant effect because Fcount more than Ftable until H1 acceptable. The best quality obtained was the Nata de leri treatment with the addition of granulated sugar and 50% dragon fruit peel extract (A2B3) with the highest average organoleptic test results. So that it can be used as a recommendation for processed products that have economic value.